Teatr i dramat rosyjski w polskich badaniach rusycystycznych - Piłat, Walenty (Studia Rossica Posnaniensia, 2016)
The article analyzes Polish studies of the Russian theater and drama of the first half of the twentieth century in the context of the Great Theater Reform, written by Katarzyna Osińska, Jadwiga Gracla, Halina Mazurek, Ludwika Mięsowska, and others. It is pointed out that the critical works of these Polish scholars bring many important conclusions concerning contemporary dramatic literature in Russia. In the past drama as a literary genre did not attract much attention from Polish Russian scholars, although in recent years the situation has changed. More and more valuable dissertations are being published on this subject.